Persons of courage and renown Tuareg actors, acting, plays, and cultural memory in northern Mali - Rasmussen, Susan J., 1949- (Lexington Books, 2019)
This book explores culture, memory, and creativity in acting and plays in Tamajaq-speaking, Muslim, semi-nomadic Tuareg society in northern Mali. Rasmussen analyzes how Tuareg actors negotiate cultural memory and encounters in communities, caught historically and currently between political violence and precarious peace.